(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
The information about unsatisfactory factors in flushing water and wastewater, which are formed on the territory of Kryvyi Rih repairmechanical plant and present threat of pollution of the Saksagan river’s surface water, is presented in the article. It has been established that there are suspended substances, sulfates, ammonium nitrogen, chlorides, nitrates, nitrites, phosphates, petroleum products, iron, zinc, aluminum, chromium and others in the structure of industrial wastewater .The presence of these chemical pollutants in an open water objectbrings threatof significant violations in the state of biogeocoenosis of reservoir.